Health, Wellness, and Place Attachment During and Post Health Pandemics - Majeed, Salman; Ramkissoon, Haywantee (Frontiers in Psychology, 2020)
Therapeutic landscapes encapsulate healing and recovery notions in natural and built environmental settings. Tourists’ perceptions determine their decision making of health and wellness tourism consumption. Researchers struggle with the conceptualization of the term ‘therapeutic landscapes’ across disciplines. Drawing on extant literature searched in nine databases, this scoping review identifies different dimensions of therapeutic landscapes. Out of identified 178 literature sources, 124 met the inclusion criteria of identified keywords. We review the contribution and the potential of environmental psychology in understanding tourist behavior to promote health and wellness tourism destinations in a post COVID-19 context. We develop and propose conceptual framework comprising: (1) perceived goodness of therapeutic landscapes, (2) health and wellness consumption, (3) COVID-19 pandemic perceived health and wellness risk, (4) place attachment (5) re-visitation. We propose measurement scales, discuss implications and major issues in the immediate and post the COVID-19 pandemic to inform future research.